Проблемы эндодонтического лечения и возможности их решения как залог качественной обтурации корневого канала (Эндодонтия Today)
The article provides analysis of the major problems in endodontics, identified the causes of treatment failures and suggests ways or their solutions. We consider such solutions to the problem of violations of the boundary seal, as the application of the method of vertical condensation and filling the root canal to the physiological apex. In the focus of scientific research are also problems of bacterial origin of periapical lesions, poor access and search of the root canal. According to specialists in endodontics, root canal filling by vertical condensation of thermoplastic gutta-percha is currently considered the most reliable.